Tracking tigers in ranthambhore - Bhardwaj, Gobind Sagar (Noida, 2008)
Set in the staggeringly beautiful environs of the Ranthambhore National Park, in the colorful Indian state of Rajasthan, Tracking Tigers in Ranthambhore is an insider's account of the lives of the regal beasts of the sub-continent. It is a wildlife tour de force, told with an extraordinary blend of fluid narrative and scientific data.
Keywords: Tigers